2019
DOI: 10.1371/journal.pgen.1008425
|View full text |Cite
|
Sign up to set email alerts
|

NusG prevents transcriptional invasion of H-NS-silenced genes

Abstract: Evolutionarily conserved NusG protein enhances bacterial RNA polymerase processivity but can also promote transcription termination by binding to, and stimulating the activity of, Rho factor. Rho terminates transcription upon anchoring to cytidine-rich motifs, the so-called Rho utilization sites (Rut) in nascent RNA. Both NusG and Rho have been implicated in the silencing of horizontally-acquired A/T-rich DNA by nucleoid structuring protein H-NS. However, the relative roles of the two proteins in H-NS-mediated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 76 publications
0
36
0
Order By: Relevance
“…Furthermore, the S. aureus Rho protein can functionally replace E. coli Rho in complementation assays [89] and the Rho proteins from both S. aureus and B. subtilis are sensitive to bicyclomycin [89,93]. Finally, recent transcriptomic studies conducted in B. subtilis [27], S. aureus [30], and M. tuberculosis [29] have revealed that rho inactivation causes genome-wide pervasive (mostly antisense) transcription in these species, a pattern remarkably similar to that found in E. coli [26] and Salmonella [28] despite significantly divergent genome organizations/compositions (e.g., GC contents of ~33% for S. aureus, ~43% for B. subtilis, 50-52% for E. coli and Salmonella, and ~66% for M. tuberculosis).…”
Section: Rho-mediated Regulatory Mechanisms In Gram-positive Bacteriamentioning
confidence: 68%
See 3 more Smart Citations
“…Furthermore, the S. aureus Rho protein can functionally replace E. coli Rho in complementation assays [89] and the Rho proteins from both S. aureus and B. subtilis are sensitive to bicyclomycin [89,93]. Finally, recent transcriptomic studies conducted in B. subtilis [27], S. aureus [30], and M. tuberculosis [29] have revealed that rho inactivation causes genome-wide pervasive (mostly antisense) transcription in these species, a pattern remarkably similar to that found in E. coli [26] and Salmonella [28] despite significantly divergent genome organizations/compositions (e.g., GC contents of ~33% for S. aureus, ~43% for B. subtilis, 50-52% for E. coli and Salmonella, and ~66% for M. tuberculosis).…”
Section: Rho-mediated Regulatory Mechanisms In Gram-positive Bacteriamentioning
confidence: 68%
“…In E. coli, Rho negatively regulates transcription of its own gene by terminating transcription at multiple sites within the 5' UTR and the initial translated portion of rho mRNA [84]. A similar feedback mechanism operates in Salmonella where finding that strains with rho mutations overproduce Rho protein suggests that a substantial level of termination occurs constitutively during the growth of wild-type cells [28]. A recent study identified rho as a regulatory target of the small RNA SraL in Salmonella.…”
Section: Regulatory Srnas As Antiterminatorsmentioning
confidence: 98%
See 2 more Smart Citations
“…Abundance of FlgM correlates with the absence of agella in the ΔyjiY supernatant treated WT cells. Since, NusG works synergistically with the global transcriptional regulator H-NS that binds speci cally to AT-rich SPIs in Salmonella genome and represses the genes 46,47 . Interestingly, in E. coli, H-NS has been linked to cell cycle, since the cells attempt to optimize H-NS concentration by maintaining a constant ratio of H-NS to chromosomal DNA in the cell 48 , which might explain the increase in cell length after ΔyjiY supernatant treatment.…”
Section: Discussionmentioning
confidence: 99%